1996
DOI: 10.1088/0268-1242/11/2/015
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the effect of surface passivant charges on HgCdTe photoconductive detectors

Abstract: The effect of fixed surface charge density (Q f ) on the performance of HgCdTe (MCT) photoconductive detectors is presented in this study. The figure of merit such as the specific detectivity (D * ) of Hg 0.78 Cd 0.22 Te photoconductive detectors operating at 77 K is calculated with 300 K background and 2π field of view (FOV). The equations leading to the above calculations are developed for the case of a one-dimensional model. Our calculations show that: (i) D * shows maxima with varying Q f ; (ii) improvemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 18 publications
1
13
0
1
Order By: Relevance
“…Passivants can also modify performance. For example, passivants for MCT photoconductive detectors give rise to positive fixed charges, which alter performance of these photoconductive detectors . Density functional theory studies have also found that absorption of transition metals on single‐layer phosphorene could hinder use of this material for spintronics applications .…”
Section: Long‐term Stable and Reliable Devicesmentioning
confidence: 99%
“…Passivants can also modify performance. For example, passivants for MCT photoconductive detectors give rise to positive fixed charges, which alter performance of these photoconductive detectors . Density functional theory studies have also found that absorption of transition metals on single‐layer phosphorene could hinder use of this material for spintronics applications .…”
Section: Long‐term Stable and Reliable Devicesmentioning
confidence: 99%
“…For higher values of SRH trap density, the non-radiative SRH lifetime dictates the effective value of the carrier lifetime. However, when interfacial surface recombination velocity is high (10 2 -10 3 m/s) (Pal et al 1996) the effective lifetime is determined by the surface recombination rather than SRH recombination via traps. The dependence of the photoconductor gain on SRH trap density and surface recombination velocity at the interfaces is shown separately in Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Detailed results on dependence of lifetime on surface conditions such as Q ss , n ss and SRV are given in Ref. [14][15][16][17]. Hence for intermediate values of u s from 20 to 50 mV there is trade-off between increasing effective lifetime and increasing n 0s which effect shunt noise in opposite directions and hence a peak near 45 mV.…”
Section: G-r Noise Model Including Shunt Resistancesmentioning
confidence: 99%
“…Additionally, Q ss is computed using results of standard one-dimensional model of MIS theory [13][14][15][16] …”
Section: Passivation Modelmentioning
confidence: 99%